Stem cell engineering in bioreactors for large‐scale bioprocessing. Issue 1 (15th August 2013) - Liu, Ning; Zang, Ru; Yang, Shang‐Tian; Li, Yan
<x xml:space="preserve">Abstract</x> Stem cells are promising cell sources for many biomedical applications including cell therapy, regenerative medicine, and drug discovery. However, the commonly used static tissue culture vessels can only generate a low number of cells. To provide an adequate number of stem cells for clinical applications, a scalable process based on bioreactors is needed. Stem cells can be either cultured as free cells/aggregates in suspension or as adherent cells on the solid substrates. Based on the cell property, different bioreactor configurations are developed to better expand stem cells while maintaining their differentiation capacity. In this review, several major types of bioreactor systems and their applications in stem cell engineering are discussed. Continued advancements in bioprocess and bioreactor research and development are important to engineer stem cells for their use in biomedical applications.